ANALISIS PERLINDUNGAN KONSUMEN PADA LEMBAGA ALTERNATIF PENYELESAIAN SENGKETA (LAPS) SEKTOR JASA KEUANGAN DI INDONESIA - Atika Ismail; Eni Suarti (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2021)
Whereas the establishment of an alternative institution for dispute resolution in the financial services sector seems to want to reduce BPSK's authority by reinforcing the boundaries between banking/non-banking consumers and other consumers that BPSK had not previously distinguished in resolving submitted disputes. However, the existence of this LAPS creates dualism in consumer dispute resolution. Moreover, the regulation regarding the LAW ERA NO.2/TH.16/OCTOBER 2016: CONSUMER DISPUTE SETTLEMENT BY THE CONSUMER DISPUTE SETTLEMENT AGENCY (BPSK) AND ALTERNATIVE DISPUTE SETTLEMENT AGENCY IN THE FINANCIAL SERVICES SECTOR (LAPS-SJK) 197 absolute authority/competence for settlement the dispute is not explicitly regulated. Until now, there are still many consumers who prefer BPSK as dispute resolution because the procedure is considered clearer and provides more protection, one of which is the application of a tiered dispute resolution mechanism. Likewise, business actors are reluctant to choose LAPS-SJK as an alternative for consumer dispute resolution and prefer to settle disputes by consensus/family deliberation. If consensus/peace is not reached, dispute resolution through the district court is the last option that will be taken by business actors to resolve disputes with consumers because it is more certain